1994
DOI: 10.1080/02773819408003083
|View full text |Cite
|
Sign up to set email alerts
|

Electron Transfer Reactions in Pulping Systems (VII): Degradation Reactions of β-Methoxy Lignin Models

Abstract: A key step in the delignification of wood is the breakage of the B-aryl ether bonds of lignin. Two mechanisms are discussed for how anthrahydroquinone (AHQ) brings about this particular fragmentation. The "adduct" mechanism involves bond formation between lignin quinonemethide (QM) intermediates and AHQ, followed by fragmentation. The other mechanism ("SET" mechanism) involves a single electron transfer between AHQ and a lignin QM followed by fragmentation. The literature concerning adducts and SET reactions i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 5 publications
(5 reference statements)
1
9
0
Order By: Relevance
“…It is suggested that AQ promotes reductive cleavage of ether bonds and simultaneously limits the degradation (peeling) of carbohydrates by operating as a redox shuttle (quinone-hydroquinone). 8,141,142 A major advantage of soda(-AQ) pulping is that a sulfur-free lignin is acquired, in contrast to kraft and sulfite pulping. 73 Soda(-AQ) lignin is typically characterised by a low b-O-4 content, 75,136,143 and can be isolated through precipitation.…”
Section: Fractionation Based On Delignificationmentioning
confidence: 99%
“…It is suggested that AQ promotes reductive cleavage of ether bonds and simultaneously limits the degradation (peeling) of carbohydrates by operating as a redox shuttle (quinone-hydroquinone). 8,141,142 A major advantage of soda(-AQ) pulping is that a sulfur-free lignin is acquired, in contrast to kraft and sulfite pulping. 73 Soda(-AQ) lignin is typically characterised by a low b-O-4 content, 75,136,143 and can be isolated through precipitation.…”
Section: Fractionation Based On Delignificationmentioning
confidence: 99%
“…The residue was crystallized from toluene to give colorless crystals, mp 96-99 °(one experiment), 86.5-88.5 °(another experiment); both sets of crystals had identical spectra: IR (mull) cm -1 3100-3600 (OH), 1600 (aryl); 1 H-NMR (CDC1 3 ) 8 2.30 (s, 3, ArCH3), 3.65 (br s, 1, OH), 3.84 (s, 3, OCH 3 ), 3.86 (s, 3, OCH 3 ), 3.85 (d of d, JAX = 9.3 and JAB = 10.0Hz, 1, ArCHxCHAHB), 4.12 (d of d, JAB = 10.0 and JBX = 3.2Hz, 1, ArCHXCHAH.B), 4.98 (d of d, JAX = 9.3 and JBX = 3.2Hz, 1, ArCHXCHAHB), 5.73 (s, 1, OH), 6.6-7.0 (m, 6, ArH); 1 3 H-NMR (d6-acetone) ppm 20.9 (q, ArCH 3 ), 56.0 (q, OCH 3 ), 72. 4 2-(2'-methoxy-4'-methylphenoxy)-l-(4'-hydroxy-3-methoxyphenyl)ethene (3a/3b). To thirteen 4.5 mL bombs was added 40 mg of 2.…”
Section: -(4'-hydroxy-3'-methoxyphenyl)-2-(2"-methoxy-4"-methylphenox...mentioning
confidence: 99%
“…The reaction mixture was treated with dimethyl sulfate, for conversion of the phenols to methyl ethers, 4 and then extracted with chloroform. The CHCl 3 solution was washed with water, dried (Na 2 SO 4 ), and analyzed by gas chromatography (Hewlett-Packard HP 5890 GC, HP-17 packed column).…”
Section: -(4'-hydroxy-3'-methoxyphenyl)-2-(2"-methoxy-4"-methylphenox...mentioning
confidence: 99%
See 1 more Smart Citation
“…Biomass is more advantageous than traditional fossil fuels because of its abundance, sustainability, and lower yield of unwanted byproducts and damaging gases when degraded . Lignin, one component of lignocellulosic biomass, is a highly branched polymer composed of three primary phenylpropane monomers ( p -coumaryl alcohol, coniferyl alcohol, and sinapyl alcohol) linked together by carbon–oxygen and carbon–carbon bonds. , The β-O-4 linkage [1-(4-hydroxy-3-methoxyphenyl)-2-(2-methoxyphenoxy)-1,3-propanediol], shown in Figure , is the most common linkage in lignin and comprises between 50 and 60% of all lignin linkages . Therefore, it is commonly used as a model compound in lignin studies.…”
Section: Introductionmentioning
confidence: 99%